Analysis of the influence of cooling jets on the wind and thermal environment in football stadiums in hot climates. (September 2020) - Zhong, Fangliang; Calautit, John K; Hughes, Ben R
After winning the bid of the FIFA's World Cup 2022, Qatar is facing the greatest challenges in terms of minimizing substantial energy consumptions for air-conditioning of stadiums and maintaining aero-thermal comfort for both players and spectators inside stadiums. This paper presents the results of temperature distributions and wind environment of the original stadium under the hot-humid climate and improvements on them for optimized scenarios of cooling jets. A combined computational fluid dynamics and building energy simulation approach was used to analyse the cooling performance and energy consumption per match of cooling air jets for 10 scenarios with different supply velocities, supply temperatures and locations of jets. The optimal scenario is to employ vertical jets above the upper tiers at supply temperature of 20°C and velocities of 2–12 m/s, integrated with horizontal jets of the same temperature at the lower tiers with 4 m/s and around the pitch with 7 m/s. This scenario can maintain the spectator tiers at an average temperature of 22°C and reduce the maximum predicted percentage of dissatisfied of thermal comfort from the original 100% to 63% for the pitch and 19% for the tiers, respectively. In terms of the energy consumption for the air-conditioning system per match, compared with one of the 2010 South Africa World Cup stadiums Royal Bafokeng stadium which consumed approximately 22.8 MWh energy for air-conditioning in winter (highest outdoor temperature 24.4°C), the maximum energy consumption of the optimal scenario in November (highest outdoor temperature 34.2°C) can reach 108 MWh. In addition, the spectator zones with scenario 8 have the potential to be resilient to the seasonal change of outdoor temperature if slight modifications of the supply velocities and precise temperature control on the spectator zones are applied. Moreover, the configurations presented in this paper can be used as a foundation of jets arrangement for future stadium retrofits in the hot climates. Practical application: This study assesses the aero-thermal conditions of a case study stadium under the hot climate of Qatar and explores the potential of applying cooling jets with different supply velocities, supply temperatures and their locations on the enhancement of both thermal and wind environment of spectator tiers and pitch. The assessment of the original stadium indicates that the ascending curved roof structure impedes the fresh air entering into the stadium and results in an asymmetric temperature distribution on the spectator tiers. The optimized design suggests a combination of vertical jets under the roof and both three arrays of horizontal jets at lower tiers and around pitch for future stadium optimizations in hot climates. It also recommends enhancing the thermal conditions on the pitch by optimizing the velocity of horizontal jets around the pitch. Moreover, the future design of the exact stadiums to be resilient to the seasonal changing outdoor temperature can be implemented based on scenario 8.